Sealing sheet and polymer composition layer

The sealing sheet with a calcium oxide-containing polymer composition layer and cross-linked olefin polymer addresses the challenge of moisture reduction in electronic device sealing without pre-drying, ensuring low moisture content and adhesive strength.

CN113969083BActive Publication Date: 2024-12-17AJINOMOTO CO INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202110824481.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-22
Filing Date
2021-07-21
Publication Date
2024-12-17
Estimated Expiration
2041-07-21

AI Technical Summary

Technical Problem

Existing sealing sheets for electronic devices require pre-drying to reduce moisture content, which is costly and difficult to implement without peeling off protective layers, especially in laminated structures with low moisture permeability.

Method used

A sealing sheet with a laminated structure comprising a support, a polymer composition layer containing 40% or more calcium oxide and an olefin polymer with a cross-linked structure, and a protective sheet, achieving a water content of 500 ppm or less in the polymer composition layer without prior drying.

Benefits of technology

The sealing sheet effectively reduces moisture content to 500 ppm or less, allowing omission of pre-drying processes and maintaining adhesive strength under high humidity and temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE005
    Figure DEST_PATH_IMAGE005
  • Figure DEST_PATH_IMAGE007
    Figure DEST_PATH_IMAGE007
  • Figure 794059DEST_PATH_IMAGE003
    Figure 794059DEST_PATH_IMAGE003
Patent Text Reader

Abstract

The present invention provides a sealing sheet in which prior drying can be omitted and the water content of a polymer composition layer is sufficiently reduced. The sealing sheet has a laminated structure including a support, a polymer composition layer and a protective sheet in sequence, the polymer composition layer includes calcium oxide and an olefin polymer having a cross-linked structure, the content of calcium oxide is 40% by mass or more relative to 100% by mass of the non-volatile components of the polymer composition layer, and the water content of the polymer composition layer is 500 ppm or less based on the mass basis relative to the entire polymer composition layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sealing sheet and a polymer composition layer useful for sealing electronic devices. Background Art

[0002] In order to protect electronic devices such as organic EL (Electroluminescence) devices and solar cells from moisture, an operation of sealing the electronic devices with a polymer composition layer is performed.

[0003] As a polymer composition layer suitable for sealing electronic devices, a layer containing a hygroscopic filler is known. For example, Patent Document 1 discloses a sealing sheet composed of a support and a polymer composition layer containing a hygroscopic metal hydroxide.

[0004] For sealing sheets (especially sealing sheets using hygroscopic fillers), in order to prevent moisture on the surface and inside of the polymer composition layer used to seal electronic devices from adversely affecting the electronic devices, the sealing sheet is dried before sealing. For example, Patent Document 2 discloses that in a method for manufacturing an organic electroluminescent element, a sealed body is simultaneously irradiated with microwaves and far infrared rays to dry the sealed body.

[0005] The sealing sheet (especially the sealing sheet using a hygroscopic filler) needs to prevent the polymer composition layer from absorbing moisture during storage. In order to prevent the polymer composition layer from absorbing moisture, for example, Patent Document 3 discloses a sealing sheet having a water vapor permeability of 1 (g / m 2 / 24hr) or less) to protect the polymer composition layer.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2017 / 057708

[0009] Patent Document 2: Japanese Patent Application Publication No. 2006-269247

[0010] Patent document 3: International Publication No. 2018 / 181426. Summary of the invention

[0011] Problems to be solved by the invention

[0012] From the perspective of reducing the manufacturing cost of electronic devices, it is desirable to omit drying of the sealing sheet before sealing (hereinafter sometimes referred to as "pre-drying"). In addition, in a sealing sheet having a laminated structure including a support with low moisture permeability, a polymer composition layer, and a protective sheet with low moisture permeability in sequence, it is difficult to pre-dry the polymer composition layer without peeling off the protective sheet. The present invention is made with a view to this situation, and an object of the present invention is to provide a sealing sheet in which pre-drying can be omitted and the water content of the polymer composition layer is sufficiently reduced.

[0013] Means used to solve problems

[0014] The present invention which can achieve the above-mentioned object is as follows.

[0015] [1] A sealing sheet having a laminated structure comprising a support, a polymer composition layer and a protective sheet in this order,

[0016] The polymer composition layer comprises an olefin polymer having a cross-linked structure and calcium oxide.

[0017] The content of calcium oxide is 40% by mass or more relative to 100% by mass of the non-volatile components of the polymer composition layer, and

[0018] The water content of the polymer composition layer is 500 ppm or less based on the mass of the entire polymer composition layer.

[0019] [2] The sealing sheet according to [1] above, wherein the content of calcium oxide is 80% by mass or less based on 100% by mass of the nonvolatile components of the polymer composition layer.

[0020] [3] The sealing sheet according to [1] or [2], wherein the olefin polymer having a crosslinked structure is formed of an olefin polymer having a carboxyl group and / or an acid anhydride group and an olefin polymer having an epoxy group.

[0021] [4] The sealing sheet according to any one of [1] to [3], wherein the water vapor permeability of the support and the protective sheet are respectively 1 (g / m 2 / 24hr) or less.

[0022] [5] The sealing sheet according to any one of [1] to [4], which is used for sealing electronic devices.

[0023] [6] The sealing sheet according to [5] above, wherein the electronic device is an organic EL device or a solar cell.

[0024] [7] a polymer composition layer comprising an olefin polymer having a cross-linked structure and calcium oxide,

[0025] The content of calcium oxide is 40% by mass or more relative to 100% by mass of the non-volatile components of the polymer composition layer, and

[0026] The water content of the polymer composition layer is 500 ppm or less based on the mass of the entire polymer composition layer.

[0027] [8] The polymer composition layer according to [7] above, wherein the content of calcium oxide is 80% by mass or less relative to 100% by mass of the nonvolatile components of the polymer composition layer.

[0028] [9] The polymer composition layer according to [7] or [8] above, wherein the olefin polymer having a cross-linked structure is formed of an olefin polymer having a carboxyl group and / or an acid anhydride group and an olefin polymer having an epoxy group.

[0029] Effects of the Invention

[0030] The water content in the polymer composition layer of the sealing sheet of the present invention is sufficiently low, and preliminary drying can be omitted. DETAILED DESCRIPTION

[0031] The present invention provides a sealing sheet having a laminated structure sequentially including a support, a polymer composition layer and a protective sheet. Other layers (such as a release layer) may be present between the support and the polymer composition layer, and between the polymer composition layer and the protective sheet. In addition, the present invention also provides the polymer composition layer itself.

[0032] It is one of the characteristics of the present invention that the water content of the polymer composition layer is 500ppm or less based on the mass basis of the polymer composition layer as a whole. As such, the sealing sheet of the present invention with a sufficiently low water content of the polymer composition layer can omit prior drying. The lower the water content, the more preferred (ideally 0ppm), based on the mass basis of the polymer composition layer as a whole, preferably 250ppm or less, more preferably 100ppm or less. The water content can be measured as described in the embodiment column described later.

[0033] One of the characteristics of the present invention is that the polymer composition layer contains a large amount of calcium oxide as a hygroscopic filler. By using a large amount of calcium oxide, the water content of the polymer composition layer can be sufficiently reduced during the production of the sealing sheet (especially during aging).

[0034] In order to fully reduce the water content of the polymer composition layer, the content of calcium oxide is 40% by mass or more, preferably 41% by mass or more, and more preferably 42% by mass or more relative to 100% by mass of the non-volatile components of the polymer composition layer. On the other hand, from the viewpoint of the adhesiveness of the polymer composition layer, the content of calcium oxide is preferably 80% by mass or less, more preferably 75% by mass or less, and further preferably 70% by mass or less relative to 100% by mass of the non-volatile components of the polymer composition layer.

[0035] Commercially available calcium oxide may be used, such as "QC-X" manufactured by Inoue Lime Industry Co., Ltd., "Moisture Top #10" manufactured by Sankyo Flour Mill Co., Ltd., "HAL-G", "HAL-J", and "HAL-F" manufactured by Yoshizawa Lime Industry Co., Ltd., and "CaO Nano Powder" manufactured by Filgen Co., Ltd.

[0036] In the present invention, a mixture containing calcium oxide can be used as a hygroscopic filler. Examples of such a mixture include burnt dolomite (a mixture containing calcium oxide and magnesium oxide). Burnt dolomite can be obtained from, for example, Yoshizawa Lime Industry Co., Ltd.

[0037] In order to prevent calcium oxide and the like from damaging electronic devices during the sealing process and to improve the interfacial bonding strength between calcium oxide and the polymer, the particle size of calcium oxide and the mixture containing calcium oxide (hereinafter sometimes referred to as "calcium oxide and the like") is preferably 0.03 to 10 μm, more preferably 0.05 to 5 μm, and further preferably 0.1 to 3 μm. These particle sizes are median particle sizes of the particle size distribution when the particle size distribution is prepared on a volume basis using laser diffraction scattering particle size distribution measurement (JIS Z 8825).

[0038] The polymer composition layer may contain a hygroscopic filler other than calcium oxide (hereinafter sometimes referred to as "other hygroscopic filler"). Examples of other hygroscopic fillers include semi-calcined hydrotalcite, calcined hydrotalcite, magnesium oxide, molecular sieves, and the like. Other hygroscopic fillers may be used alone or in combination of two or more. The content of the hygroscopic filler other than calcium oxide is preferably 0 to 40% by mass, preferably 0 to 30% by mass, and more preferably 0 to 20% by mass relative to 100% by mass of the non-volatile component of the polymer composition layer.

[0039] It is one of the characteristics of the present invention that the polymer composition layer contains an olefin polymer having a crosslinked structure (hereinafter sometimes referred to as a "crosslinked olefin polymer"). By using such a crosslinked olefin polymer, a polymer composition layer can be obtained that can suppress the decrease in adhesive strength even when stored under high humidity and high temperature conditions (i.e., has good moisture and heat resistance). The crosslinked olefin polymer may be used alone or in combination of two or more.

[0040] From the viewpoint of moist heat resistance, the content of the crosslinked olefin polymer is preferably 1 to 40% by mass, more preferably 2 to 35% by mass, and even more preferably 3 to 30% by mass based on 100% by mass of the nonvolatile components of the polymer composition layer.

[0041] The cross-linked olefin polymer is preferably formed of an olefin polymer having a carboxyl group and / or an acid anhydride group (i.e., a carbonyloxycarbonyl group (-CO-O-CO-)) and an olefin polymer having an epoxy group, and more preferably formed of an olefin polymer having an acid anhydride group and an olefin polymer having an epoxy group. The olefin polymer having a carboxyl group and / or an acid anhydride group and the olefin polymer having an epoxy group may be used alone or in combination of two or more.

[0042] Hereinafter, the “olefin-based polymer” portion including the crosslinked olefin-based polymer, the olefin-based polymer having a carboxyl group and / or anhydride group, and the olefin-based polymer having an epoxy group will be described.

[0043] The olefin units of the olefin polymer are preferably units derived from monoolefins having one olefinic carbon-carbon double bond and / or dienes having two olefinic carbon-carbon double bonds. Examples of the monoolefins include α-olefins such as ethylene, propylene, 1-butene, isobutylene (isobutylene), 1-pentene, 1-hexene, 1-heptene, and 1-octene. Examples of the dienes include 1,3-butadiene, isoprene, 1,3-pentadiene, and 2,3-dimethylbutadiene.

[0044] The olefin polymer may be a homopolymer, or a copolymer such as a random copolymer or a block copolymer. As copolymers, copolymers of two or more olefins may be listed; and copolymers of olefins and monomers other than olefins such as non-conjugated dienes and styrene may be listed. Examples of preferred copolymers include ethylene-non-conjugated diene copolymers, ethylene-propylene copolymers, ethylene-propylene-non-conjugated diene copolymers, ethylene-butene copolymers, propylene-butene copolymers, propylene-butene-non-conjugated diene copolymers, styrene-isobutylene copolymers, styrene-isobutylene-styrene copolymers, isobutylene-isoprene copolymers, and the like.

[0045] As olefin polymers, butene polymers and propylene polymers are preferred. Here, "butene polymer" refers to a polymer in which the main unit (the unit with the largest content) among all olefin monomer units constituting the polymer is derived from butene. As butene, for example, 1-butene, isobutylene (isobutylene) and the like can be cited. "Propylene polymer" refers to a polymer in which the main unit (the unit with the largest content) among all olefin monomer units constituting the polymer is derived from propylene.

[0046] When the butene polymer is a copolymer, examples of the monomer other than butene include styrene, ethylene, propylene, isoprene, etc. When the propylene polymer is a copolymer, examples of the monomer other than propylene include ethylene, butene, isoprene, etc.

[0047] From the viewpoint of suppressing the decrease in fluidity due to thickening of the varnish, the olefin polymer is preferably amorphous. Here, amorphous means that the olefin polymer does not have a clear melting point, and for example, a material in which no clear peak is observed when the melting point is measured by DSC (differential scanning calorimetry) of the olefin polymer can be used.

[0048] Next, the olefin polymer having a carboxyl group and / or anhydride group is described. As the anhydride group, for example, a group derived from succinic anhydride, a group derived from maleic anhydride, a group derived from glutaric anhydride, etc. can be cited. As the olefin polymer having a carboxyl group and / or anhydride group, preferably a butene polymer having a carboxyl group and / or anhydride group, and a propylene polymer having a carboxyl group and / or anhydride group, more preferably a butene polymer having anhydride group and a propylene polymer having anhydride group.

[0049] The carboxyl group concentration in the olefin polymer having a carboxyl group is preferably 0.05 to 10 mmol / g, more preferably 0.1 to 5 mmol / g. The carboxyl group concentration is obtained from the acid value defined as the number of mg of potassium hydroxide required to neutralize the acid present in 1 g of the polymer according to JIS K 2501.

[0050] The acid anhydride group concentration in the olefin polymer having an acid anhydride group is preferably 0.05 to 10 mmol / g, more preferably 0.1 to 5 mmol / g. The acid anhydride group concentration is obtained from the acid value defined as the number of mg of potassium hydroxide required to neutralize the acid present in 1 g of the polymer according to JIS K 2501.

[0051] The total of the carboxyl group concentration and the acid anhydride group concentration in the olefin polymer having both carboxyl groups and acid anhydride groups is preferably 0.05 to 10 mmol / g, more preferably 0.1 to 5 mmol / g.

[0052] The olefin polymer having a carboxyl group and / or anhydride group can be obtained by, for example, grafting the olefin polymer with an unsaturated compound having a carboxyl group and / or anhydride group under free radical reaction conditions. In addition, the olefin polymer having anhydride group can be obtained by free radical copolymerization of the unsaturated compound having a carboxyl group and / or anhydride group with an olefin or the like.

[0053] As the olefin polymer having a carboxyl group and / or anhydride group, for example, a polymer available from a manufacturer such as Starlight PMC Co., Ltd. can be used. Examples of such polymers include "T-YP279" manufactured by Starlight PMC Co., Ltd. (maleic anhydride-modified propylene-butene random copolymer, the amount of butene units in the total of propylene units and butene units: 36% by mass, acid anhydride group concentration: 0.464 mmol / g, number average molecular weight: 35,000), "T-YP312" manufactured by Starlight PMC Co., Ltd. (maleic anhydride-modified propylene-butene random copolymer, the amount of butene units in the total of propylene units and butene units: 29% by mass, acid anhydride group concentration: 0.464 mmol / g, number average molecular weight: 60 ,900), "ER661" manufactured by Starlight PMC (maleic anhydride-modified isobutylene-isoprene random copolymer, anhydride group concentration: 0.87 mmol / g, number average molecular weight: 39,700), "HV-300M" manufactured by Toho Chemical Industry Co., Ltd. (a modified product of maleic anhydride-modified liquid polybutene ("HV-300" (number average molecular weight: 1,400)), number average molecular weight: 2,100, number of carboxyl groups constituting the anhydride group: 3.2 / 1 molecule, acid value: 43.4 mgKOH / g, anhydride group concentration: 0.77 mmol / g), etc.

[0054] Next, the olefinic polymer having an epoxy group will be described. As the olefinic polymer having an epoxy group, a butene-based polymer having an epoxy group and a propylene-based polymer having an epoxy group are preferred.

[0055] The epoxy group concentration in the olefin polymer having an epoxy group is preferably 0.05 to 10 mmol / g, more preferably 0.1 to 5 mmol / g. The epoxy group concentration is determined from the epoxy equivalent obtained in accordance with JIS K 7236-1995.

[0056] The olefin polymer having an epoxy group can be obtained by, for example, grafting an olefin polymer with an unsaturated compound having an epoxy group, such as glycidyl (meth)acrylate, 4-hydroxybutyl acrylate glycidyl ether, or allyl glycidyl ether, under free radical reaction conditions. In addition, the olefin polymer having an epoxy group can be obtained by free radical copolymerization of an unsaturated compound having an epoxy group with an olefin or the like.

[0057] Examples of olefin polymers having epoxy groups include polymers available from manufacturers such as Starlight PMC. Examples of such polymers include "T-YP341" manufactured by Starlight PMC (glycidyl methacrylate-modified propylene-butene random copolymer, the amount of butene units in the total of propylene units and butene units: 29% by mass, epoxy group concentration: 0.638 mmol / g, number average molecular weight: 155,000), "T-YP276" manufactured by Starlight PMC (glycidyl methacrylate-modified propylene-butene random copolymer, the amount of butene units in the total of propylene units and butene units: 36% by mass, epoxy group concentration: 0.638 mmol / g, number average molecular weight: 155,000). mol / g, number average molecular weight: 57,000), "T-YP313" manufactured by Xingguang PMC (methacrylate glycidyl modified propylene-butene random copolymer, the amount of butene units in the total of propylene units and butene units: 29% by mass, epoxy group concentration: 0.638 mmol / g, number average molecular weight: 155,000), "ER850" manufactured by Xingguang PMC (methacrylate glycidyl modified isobutylene-isoprene random copolymer, epoxy group concentration: 0.654 mmol / g, number average molecular weight: 99,200), etc.

[0058] The amounts of the olefin polymer having a carboxyl group and the olefin polymer having an epoxy group used are not particularly limited as long as a cross-linked structure can be formed, but the ratio of the amount (mol) of the epoxy group to the amount (mol) of the carboxyl group (i.e., the amount (mol) of the epoxy group: the amount (mol) of the carboxyl group) is preferably 100:10 to 100:500, more preferably 100:25 to 100:475, and even more preferably 100:40 to 100:450.

[0059] The amounts of the olefin polymer having an acid anhydride group and the olefin polymer having an epoxy group used are not particularly limited as long as a cross-linked structure can be formed, but the ratio of the amount (mol) of the epoxy group to the amount (mol) of the acid anhydride group (i.e., the amount (mol) of the epoxy group: the amount (mol) of the acid anhydride group) is preferably 100:10 to 100:500, more preferably 100:25 to 100:475, and even more preferably 100:40 to 100:450.

[0060] The amounts of the olefin polymer having both a carboxyl group and an acid anhydride group and the olefin polymer having an epoxy group used are not particularly limited as long as a cross-linked structure can be formed, and the ratio of "the amount of epoxy groups (mol)" to "the total amount of carboxyl groups (mol) and the amount of acid anhydride groups (mol)" (i.e., the amount of epoxy groups (mol): (the amount of carboxyl groups (mol) + the amount of acid anhydride groups (mol))) is preferably 100:10 to 100:500, more preferably 100:25 to 100:475, and even more preferably 100:40 to 100:450.

[0061] From the viewpoint of adhesiveness and flexibility, the polymer composition layer preferably contains an olefin polymer having no crosslinking structure (hereinafter sometimes referred to as "non-crosslinked olefin polymer"). The non-crosslinked olefin polymer may be used alone or in combination of two or more. The description of the "olefin polymer" part of the non-crosslinked olefin polymer is the same as the description of the "olefin polymer" part of the crosslinked olefin polymer, etc.

[0062] From the viewpoint of adhesiveness and flexibility of the polymer composition layer, the content of the non-crosslinked olefin polymer is preferably 5 to 50% by mass, more preferably 10 to 45% by mass, and even more preferably 15 to 40% by mass based on 100% by mass of the nonvolatile component of the polymer composition layer.

[0063] As the non-crosslinked olefin-based polymer, a commercially available product can be used. Examples of commercially available products thereof include “HV-300” (liquid polybutene, number average molecular weight: 1,400) manufactured by ENEOS, “HV-1900” (liquid polybutene, number average molecular weight: 2,900) manufactured by ENEOS, “X1102C” (propylene-butene random copolymer, amount of butene units in the total of propylene units and butene units: 29% by mass) manufactured by Mitsui Chemicals, Inc., “Optinal B100” (polyisobutylene, viscosity average molecular weight: 1,110,000) manufactured by BASF, “N50SF” (polyisobutylene, viscosity average molecular weight: 400,000) manufactured by BASF, “Tetrax 3T” (polyisobutylene, viscosity average molecular weight: 30,000) manufactured by ENEOS, and “Tetrax 6T” (polyisobutylene, viscosity average molecular weight: 60,000) manufactured by ENEOS.

[0064] From the viewpoint of good coating properties of the varnish of the polymer composition, the number average molecular weight of the above-mentioned olefin polymer having an acid anhydride group, the olefin polymer having an epoxy group, and the non-crosslinked olefin polymer is preferably 1,000,000 or less, more preferably 750,000 or less, further preferably 500,000 or less, further preferably 400,000 or less, further preferably 300,000 or less, and particularly preferably 200,000 or less. On the other hand, from the viewpoint of preventing the varnish of the polymer composition from being repelled during coating, showing the sealing performance of the formed polymer composition layer, and improving the mechanical strength, the number average molecular weight is preferably 1,000 or more, more preferably 2,000 or more. It should be noted that the number average molecular weight in the present invention is measured by gel permeation chromatography (GPC) method (polystyrene conversion). Specifically, the number average molecular weight based on the GPC method can be calculated as follows: use "LC-9A / RID-6A" manufactured by Shimadzu Corporation as a measuring apparatus, use "Shodex K-800P / K-804L / K-804L" manufactured by Showa Denko K.K. as a column, use toluene or the like as a mobile phase, measure at a column temperature of 40°C, and calculate using a standard curve of standard polystyrene.

[0065] The polymer composition layer may contain components other than the above (hereinafter sometimes referred to as "other components") within the range that does not impair the effects of the present invention. Other components include, for example, tackifiers, curing accelerators, antioxidants, plasticizers, etc. These may be used alone or in combination of two or more.

[0066] The tackifier is a component that imparts adhesiveness to the polymer composition layer. Examples of the tackifier include rosin resins, terpene resins, modified terpene resins (hydrogenated terpene resins, terpene-phenol copolymer resins, aromatic modified terpene resins, etc.), petroleum resins (aliphatic petroleum resins, hydrogenated petroleum resins, alicyclic petroleum resins, aromatic petroleum resins, copolymerized petroleum resins), coumarone-indene resins, alkylphenol-formaldehyde resins, xylene resins, etc.

[0067] As the thickening agent, commercially available products can be used. Examples of commercially available products include the following. Examples of rosin-based resins include, for example, Polycondensate ME-H, Polycondensate ME-D, and Polycondensate.ンクリスタルME-G, パインクリスタルKR-85, パインクリスタルKE-311, パインクリスタルKE-359、パインクリスタルD-6011、パインクリスタルPE-590、パインククスタルKE-604, パインククスタルPR-580 (both manufactured by Arakawa Chemical Industry Co., Ltd.), etc.

[0068] Examples of the terpene resin include YSレジンPX1000, YSレジンPX1150, YSレジンPX1150N, and YSレジンPX1 250, YSレジンTH130, YSレジンTR105, YSレジンLP, YSレジンCP (all made by ヤスハラケミカル Company), etc.

[0069] Examples of hydrogenated terpene resins include the Kuronol P, Kuronan M, and Kuron K series (all manufactured by Yukaron Co., Ltd.).

[0070] Terpene phenol copolymer resins include, for example, YS Polysac 2000, Polysac U, and Riser T, Riser S, Riser G (all manufactured by Römer Co., Ltd.), etc.

[0071] Examples of the aromatic modified terpene resin include YS Retin TO85, YS Retin TO105, YS Retin TO115, and YS Retin TO125 (all manufactured by Yashara Chemical Co., Ltd.).

[0072] Examples of hydrogenated petroleum resins include Escorez 5300 series and 5600 series (all manufactured by Ecoson Model Co., Ltd.); T-REZ OP501, T-REZ PR803, T-REZ HA085, T-REZ HA103, T-REZ HA105, and T-REZ HA125 (all hydrogenated dicyclopentadiene petroleum resins, manufactured by ENEOS); Quintone 1325 and Quintone 1345 (all manufactured by ZEON Corporation of Japan); IMAX S-100, IMAX S-110, IMAX P-100, IMAX P-125, and IMAX P-140 (all hydrogenated dicyclopentadiene petroleum resins, manufactured by ENEOS); Cyclopentadiene-based petroleum resin, manufactured by Idemitsu Kosan Co., Ltd.); アルコP-90, アルコP-100, アルコP-115, アルコP-125, アルコP-1 40. アルコンM-90, アルコンM-100, アルコンM-115, アルコンM-135, TFS13-030 (all manufactured by Arakawa Chemical Industry Co., Ltd.), etc.

[0073] Examples of aromatic petroleum resins include ENDEX 155 (manufactured by Etruscan Co., Ltd.); Nemesis L-90, Nemesis 120, and Nemesis 130, ネオポリマー140, ネオポリマー150, ネオポリマー17 0S, ネオポリマー160, ネオポリマーE-100, ネオポリマーE- 130. ネオポリマーM-1, ネオポリマーS, ネオポリマーS100 , ネオポリマー120S, ネオポリマー130S, ネオポリマーEP- 140 (all made by ENEOS); Tosho LX, Tosho 120, Tosho 130, Tosoh 140 (all made by Tosoh); T-REZ RB093, T-REZ RC100, T-REZ RC115, T-REZ RC093, T-REZ RE100 (all made by ENEOS), etc.

[0074] Examples of copolymerized petroleum resins include T-REZ HB103, T-REZ HB125, T-REZ PR801, T-REZPR802, and T-REZ RD104 (all made by ENEOS); Toto 60, Toto 70, Toto 90, Toto 90HS , ペトロタック90V, ペトロタック100V (all made by Tosoh Corporation); QuintoneD100 (made by Japan ZEON Corporation), etc.

[0075] From the viewpoint of heat resistance of the polymer composition layer, the softening point of the tackifier is preferably 50 to 200° C., more preferably 90 to 180° C., and even more preferably 100 to 150° C. The softening point is measured by a ring and ball method in accordance with JIS K2207.

[0076] From the viewpoint of adhesiveness and sealing properties of the polymer composition layer, the content of the tackifier is preferably 0 to 50% by mass, more preferably 0 to 40% by mass, and even more preferably 0 to 30% by mass based on 100% by mass of the nonvolatile components of the polymer composition layer.

[0077] Examples of the curing accelerator include imidazole compounds, tertiary amine / quaternary amine compounds, dimethyl urea compounds, and organic phosphine compounds.

[0078] Examples of the imidazole compound include 1H-imidazole, 2-methylimidazole, 2-phenyl-4-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 2,4-diamino-6-(2'-undecylimidazolyl-(1'))-ethyl-s-triazine, 2-phenyl-4,5-diamino-2-ethyl-4-methylimidazole, 2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate ...imidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyano (Hydroxymethyl)imidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 2-phenylimidazole, 2-dodecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,4-diamino-6-(2'-methylimidazolyl-(1'))-ethyl-s-triazine, 2,4-diamino-6-(2'-methylimidazolyl-(1'))-ethyl-s-triazine isocyanuric acid adduct, etc. Specific examples of the imidazole compound include Cuazele 2MZ, 2P4MZ, 2E4MZ, 2E4MZ-CN, C11Z, C11Z-CN, C11Z-CNS, C11Z-A, 2PHZ, 1B2MZ, 1B2PZ, 2PZ, C17Z, 1.2DMZ, 2P4MHZ-PW, 2MZ-A, and 2MA-OK (all manufactured by Shikoku Chemical Industries, Ltd.).

[0079] The tertiary amine / quaternary amine compound is not particularly limited, and examples thereof include quaternary ammonium salts such as tetramethylammonium bromide and tetrabutylammonium bromide; diazabicyclic compounds such as DBU (1,8-diazabicyclo[5.4.0]undecene-7), DBN (1,5-diazabicyclo[4.3.0]nonene-5), DBU-phenolate, DBU-octanoate, DBU-p-toluenesulfonate, DBU-formate, and DBU-phenol novolac resin salt; tertiary amines such as benzyldimethylamine, 2-(dimethylaminomethyl)phenol, and 2,4,6-tris(dimethylaminomethyl)phenol (TAP) or salts thereof; and dimethyl urea compounds such as aromatic dimethyl urea and aliphatic dimethyl urea.

[0080] Examples of the dimethyl urea compound include DCMU (3-(3,4-dichlorophenyl)-1,1-dimethylurea), aromatic dimethyl ureas such as U-CAT3512T (manufactured by Sanapro Co., Ltd.), and aliphatic dimethyl ureas such as U-CAT3503N (manufactured by Sanapro Co., Ltd.). Among them, aromatic dimethyl ureas are preferably used from the viewpoint of curability.

[0081] Examples of the organic phosphine compound include triphenylphosphine, tetraphenylphosphonium tetra-p-tolyl borate, tetraphenylphosphonium tetraphenyl borate, tri-tert-butylphosphonium tetraphenyl borate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, triphenylphosphine triphenylborane, etc. Specific examples of the organic phosphine compound include TPP, TPP-MK, TPP-K, TTBuP-K, TPP-SCN, TPP-S (all manufactured by Hokko Chemical Industry Co., Ltd.), etc.

[0082] When a curing accelerator is used, the content thereof is preferably 0.001 to 5 mass %, more preferably 0.001 to 2.5 mass %, and even more preferably 0.001 to 1 mass % based on 100 mass % of the nonvolatile components of the polymer composition layer in order to promote the formation of the olefin polymer having a crosslinked structure.

[0083] In the present invention, the antioxidant is not particularly limited, and a known antioxidant can be used. When an antioxidant is used, its content is preferably 0.01 to 5% by mass, more preferably 0.05 to 2.5% by mass, and further preferably 0.1 to 2% by mass relative to 100% by mass of the non-volatile component of the polymer composition layer.

[0084] Examples of the plasticizer include mineral oils such as paraffinic process oils, cycloparaffinic process oils, liquid paraffin, and vaseline; and vegetable oils such as castor oil, cottonseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, and olive oil.

[0085] The sealing sheet of the present invention has a laminated structure including a support, a polymer composition layer and a protective sheet in this order. Examples of the support and the protective sheet include polyolefins such as polyethylene, polypropylene, and polyvinyl chloride; cycloolefin polymers; polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate; polycarbonate; plastic films such as polyimide, etc. The support and the protective sheet may both be single-layer films or laminated films.

[0086] For the protective sheet, the surface in contact with the polymer composition layer is preferably subjected to a demolding treatment. On the other hand, the support may or may not be subjected to a demolding treatment. As the demolding treatment, for example, a demolding treatment based on a demolding agent such as a silicone resin-based demolding agent, an alkyd resin-based demolding agent, or a fluororesin-based demolding agent can be cited.

[0087] The thickness of the support and the protective sheet is not particularly limited. From the viewpoint of the handling property of the sealing sheet, they are preferably 10 to 150 μm, and more preferably 20 to 100 μm, respectively. It should be noted that when the support and the protective sheet are laminated films, the aforementioned thickness is the thickness of the laminated film. On the other hand, from the viewpoint of sealing property, the thickness of the polymer composition layer is preferably 5 to 200 μm, more preferably 5 to 150 μm, and further preferably 5 to 100 μm.

[0088] The water vapor permeability (hereinafter sometimes referred to as "WVTR") of the support and the protective sheet is preferably 1 (g / m 2 / 24hr) or less. Here, the water vapor permeability (g / m 2 " / 24hr)" means: under the conditions of temperature and humidity specified below, the penetration area is 1m within 24 hours. 2 The amount of water vapor in the sheet (g). By using a sheet with a water vapor permeability of 1 (g / m 2 / 24hr) or less, and a low moisture permeability protective sheet can prevent the polymer composition layer from absorbing moisture during the storage of the sealing sheet. It should be noted that if a low moisture permeability support and a low moisture permeability protective sheet are used, it is usually difficult to dry the sealing sheet in advance. In this regard, in the present invention, by using a large amount of calcium oxide as described above, the water content of the polymer composition layer can be fully reduced during the manufacture of the sealing sheet (especially during aging), so that the prior drying of the sealing sheet can be omitted.

[0089] The water vapor permeability of the sheet (g / m 2 / 24hr) can be measured using the water vapor transmission rate measuring device PERMATRAN series (based on ISO 15106-2, JIS K7129B) manufactured by MOCON. Specifically, the sheet is cut into 50 cm 2 After installing it on the fixture using silicone grease, use ultrapure water and adjust the temperature to 40 degrees and the humidity to 90% RH, and measure until the water vapor permeability reaches a stable state.

[0090] As a low moisture permeability support and a low moisture permeability protective sheet, for example, a film having a barrier layer or a laminated film of a film having a barrier layer and other films can be used. As the barrier layer, inorganic films such as silicon dioxide vapor-deposited films, silicon nitride films, and silicon oxide films can be cited. The barrier layer can be composed of a multilayer of multiple inorganic films (for example, silicon dioxide vapor-deposited films). In addition, the barrier layer can be composed of an organic substance and an inorganic substance, or a composite multilayer of an organic layer and an inorganic film.

[0091] As a film having a barrier layer, for example, a film having a WVTR of 0.0005 (g / m 2 / 24hr) or less high barrier plastic film. As high barrier plastic film, for example, a film made by stacking a single layer or multiple layers of inorganic films such as silicon oxide (silicon dioxide), aluminum oxide, magnesium oxide, silicon nitride, silicon oxide nitride, SiCN, amorphous silicon on the surface of a plastic film by using a chemical vapor growth method (for example, a chemical vapor growth method based on heat, plasma, ultraviolet light, vacuum heat, vacuum plasma or vacuum ultraviolet light) or a physical vapor growth method (for example, vacuum evaporation, sputtering, ion plating, laser deposition, molecular beam epitaxy, etc.) (for example, refer to Japanese Patent Publication No. 2016-185705, Japanese Patent Publication No. 5719106, Japanese Patent Publication No. 5712509, Japanese Patent Publication No. 5292358, etc.). In order to prevent cracks in the inorganic film, it is preferred that the inorganic film and the transparent planarization layer (for example, a transparent plastic layer) are alternately stacked.

[0092] In addition, as a film having a barrier layer, for example, a film having a WVTR of 0.01 (g / m 2 / 24hr) or more and 1 (g / m 2 / 24hr) or less. Examples of medium barrier plastic films include films produced by, for example, the following methods: a method of vapor-depositing an inorganic film containing inorganic substances such as silicon oxide (silicon dioxide), aluminum oxide, magnesium oxide, silicon nitride, silicon oxynitride, SiCN, and amorphous silicon on the surface of a substrate as a barrier layer; or a method of coating a coating liquid containing a metal oxide and an organic resin having barrier properties on a substrate and drying the coating liquid (for example, see Japanese Patent Publication No. 2013-108103, Japanese Patent Publication No. 4028353, etc.).

[0093] As a film having a barrier layer, commercial products can be used. Commercial products of medium barrier plastic films include, for example, "Clarista CI" manufactured by Clare Corporation, "Techbaria HX", "Techbaria LX" and "Techbaria L" manufactured by Mitsubishi Chemical Corporation, "IB-PET-PXB" manufactured by Dai Nippon Printing Co., Ltd., and "GL, GX series" manufactured by Toppan Printing Co., Ltd. Commercial products of high barrier plastic films include, for example, "X-BARRIER" manufactured by Mitsubishi Chemical Corporation.

[0094] The sealing sheet and polymer composition layer of the present invention can be produced by, for example, the following operations: (1) dissolving or dispersing the above-mentioned components in an organic solvent to prepare a varnish of the polymer composition; (2) coating the obtained varnish on a support to form a coating film; (3) drying the obtained coating film to form a polymer composition layer (dried coating film); (4) laminating a protective sheet on the obtained polymer composition layer to form a laminate; and (5) heating and aging the obtained laminate to reduce the water content of the polymer composition layer.

[0095] As organic solvents that can be used to prepare varnishes, ketones such as acetone, methyl ethyl ketone, and cyclohexanone can be listed; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; cellosolves such as cellosolves; carbitols such as butyl carbitol; aromatic hydrocarbons such as toluene and xylene; dimethylformamide, dimethylacetamide, N-methylpyrrolidoneamides, etc. Only one organic solvent can be used, or two or more organic solvents can be used in combination. As organic solvents, commercial products can be used. As commercial products thereof, for example, "スワゾール" manufactured by Maruzen Petrochemical Co., Ltd. and "イプゾール" manufactured by Idemitsu Kosan Co., Ltd. can be listed. The coating of the varnish can be carried out by a known method (for example, a method using a die coater), and the coating method is not particularly limited.

[0096] In order to form an olefin polymer having a crosslinked structure, the coating is preferably dried by heating. The coating is preferably dried at a temperature of 50 to 200° C., more preferably 80 to 150° C., for a time of 1 to 60 minutes, more preferably 10 to 30 minutes. Drying may be performed under normal pressure or under reduced pressure.

[0097] The protective sheet can be laminated on the polymer composition layer using a known device, such as a roll laminator, a press, or a vacuum pressure laminator.

[0098] The aging temperature of the laminate is preferably 80 to 200° C., more preferably 100 to 150° C., and the aging time is preferably 10 to 240 minutes, more preferably 30 to 180 minutes.

[0099] The sealing sheet of the present invention can be used for sealing electronic devices. As electronic devices, for example, organic EL devices, solar cells, sensor devices, etc. can be listed. The electronic device is more preferably an electronic device that is not resistant to moisture, such as an organic EL device or a solar cell. In addition, the sealing sheet of the present invention can be used for sealing a conductive substrate, etc. Example

[0100] Hereinafter, examples are given to more specifically illustrate the present invention, but the present invention is not limited to the following examples, and can also be implemented by appropriately applying changes within the scope that can meet the above / below purport, and they are all included in the technical scope of the present invention. It should be noted that the "parts" and "%" in the amount of the components and the amount of the copolymerization unit refer to "parts by mass" and "% by mass" respectively unless otherwise specified.

[0101] <ingredients>

[0102] The components used in Examples and Comparative Examples are shown below.

[0103] (Olefin polymers)

[0104] "T-YP341" (produced by Seikyo PMC, glycidyl methacrylate-modified propylene-butene random copolymer, propylene unit / butene unit: 71% / 29%, epoxy group concentration: 0.64 mmol / g, number average molecular weight: 155,000)

[0105] "HV-300M" (manufactured by Toho Chemical Industry Co., Ltd., maleic anhydride-modified liquid polybutene, anhydride group concentration: 0.77 mmol / g, number average molecular weight: 2,100)

[0106] "HV-1900" (manufactured by ENEOS, liquid polybutene, number average molecular weight: 2,900)

[0107] (Hygroscopic filler)

[0108] Calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd., median particle size: 2.1 μm)

[0109] Calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd., median particle size: 1.8 μm)

[0110] Semi-calcined hydrotalcite ("DHT-4C" manufactured by Kyowa Chemical Industry Co., Ltd., particle size (median particle size): 400 nm, BET specific surface area: 15 m 2 / g)

[0111] Calcined hydrotalcite ("KW2200" manufactured by Kyowa Chemical Industry Co., Ltd., particle size (median particle size): 400 nm, BET specific surface area: 190 m 2 / g)

[0112] Magnesium oxide ("DIPSERMAG" manufactured by Tateho Chemical Industries, Ltd.)

[0113] Molecular sieve 4A (manufactured by Union Showa Co., Ltd.)

[0114] (Thickener)

[0115] "T-REZ HA105" (manufactured by ENEOS, hydrogenated alicyclic petroleum resin, softening point: 105°C)

[0116] (Antioxidant)

[0117] "Irganox 1010" (manufactured by BASF, hindered phenol antioxidant)

[0118] (Curing accelerator)

[0119] 2,4,6-Tris(dimethylaminomethyl)phenol (hereinafter abbreviated as "TAP") (manufactured by Kayaku Nureion Co., Ltd.)

[0120] <Example 1>

[0121] According to the following steps, a varnish having a mixing ratio shown in the following table is prepared, and the obtained varnish is used to prepare a sealing sheet. It should be noted that the amount (parts) of each component recorded in the following table represents the amount of non-volatile components of each component in the varnish. In addition, the following table shows the amount of hygroscopic filler added relative to 100% by mass of the non-volatile components of the varnish.

[0122] Specifically, maleic anhydride-modified liquid polybutene ("HV-300M" manufactured by Toho Chemical Industry Co., Ltd.), liquid polybutene ("HV-1900" manufactured by ENEOS Corporation), and calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd., median particle size: 2.1 μm) were dispersed in a swasole solution (non-volatile content: 60%) of a hydrogenated alicyclic petroleum resin (tackifier, "T-REZHA105" manufactured by ENEOS Corporation) using a three-roll mill to obtain a mixture. To the obtained mixture, a swasol solution (non-volatile content: 15%) of a glycidyl methacrylate-modified propylene-butene random copolymer ("T-YP341" manufactured by Seikyo PMC Co., Ltd.), a hindered phenol-based antioxidant ("Irganox 1010" manufactured by BASF), a curing accelerator (TAP, manufactured by Kayaku Nureion Co., Ltd.) and toluene were added, and the obtained mixture was uniformly dispersed using a high-speed rotary stirrer to obtain a varnish (non-volatile content: 63%) of a polymer composition.

[0123] A polyethylene terephthalate film ("SP4020" manufactured by Toyo Cross Co., Ltd., PET film thickness: 50 μm) treated on one side with a silicone-based release agent and a low moisture-permeable polyethylene terephthalate film ("Techbaria HX" manufactured by Mitsubishi Chemical Co., Ltd., PET film thickness: 12 μm) were laminated together so that the surface of SP4020 not treated with the silicone-based release agent was in contact with Techbaria HX, thereby preparing a laminated film, which was used as a support and protective sheet for a sealing sheet (laminated film thickness: 62 μm, laminated film water vapor permeability: 0.12 (g / m 2 / 24hr)). Hereinafter, the "surface of the laminate film treated with the silicone-based release agent" is referred to as the "release-treated surface".

[0124] The varnish of the polymer composition was uniformly applied on the release-treated surface of the first laminated film using a die coater and heated at 140° C. for 30 minutes to form a polymer composition layer containing an olefin polymer having a crosslinked structure.

[0125] Thereafter, the second laminated film was laminated in such a manner that its release-treated surface was in contact with the polymer composition layer, and then heated (aged) at 130° C. for 60 minutes to reduce the moisture content of the polymer composition layer, thereby obtaining a sealing sheet having a laminated structure of “support (laminated film) / polymer composition layer / protective sheet (laminated film)” (thickness of the polymer composition layer: 50 μm).

[0126] <Example 2>

[0127] A polymer composition varnish and a sealing sheet having a 50 μm thick polymer composition layer were prepared in the same manner as in Example 1 except that the amount of calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd., median particle size: 2.1 μm) was changed from 200 parts to 260 parts.

[0128] <Example 3>

[0129] A polymer composition varnish and a sealing sheet having a 50 μm thick polymer composition layer were prepared in the same manner as in Example 1 except that the amount of calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd., median particle size: 2.1 μm) was changed from 200 parts to 390 parts.

[0130] <Example 4>

[0131] A polymer composition varnish and a sealing sheet having a 50 μm thick polymer composition layer were prepared in the same manner as in Example 1 except that calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd., median particle size: 2.1 μm) was replaced with calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd., median particle size: 1.8 μm).

[0132] <Comparative Example 1>

[0133] A polymer composition varnish and a sealing sheet having a 50 μm thick polymer composition layer were prepared in the same manner as in Example 1, except that the hygroscopic filler was changed from calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd., median particle size: 2.1 μm) to semi-calcined hydrotalcite ("DHT-4C" manufactured by Kyowa Chemical Industry Co., Ltd.).

[0134] <Comparative Example 2>

[0135] A polymer composition varnish and a sealing sheet having a 50 μm thick polymer composition layer were prepared in the same manner as in Example 1 except that the hygroscopic filler was changed from calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd., median particle size: 2.1 μm) to calcined hydrotalcite (“KW2200” manufactured by Kyowa Chemical Industry Co., Ltd.).

[0136] <Comparative Example 3>

[0137] A polymer composition varnish and a sealing sheet having a 50 μm thick polymer composition layer were prepared in the same manner as in Example 1 except that the hygroscopic filler was changed from calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd., median particle size: 2.1 μm) to magnesium oxide (“DISPERMAG” manufactured by Tateho Chemical Industries, Ltd.).

[0138] <Comparative Example 4>

[0139] A polymer composition varnish and a sealing sheet having a 50 μm thick polymer composition layer were prepared in the same manner as in Example 1 except that the hygroscopic filler was changed from calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd., median particle size: 2.1 μm) to molecular sieve 4A (manufactured by Union Showa Co., Ltd.).

[0140] <Comparative Example 5>

[0141] A varnish of a polymer composition and a sealing sheet of a polymer composition having a thickness of 50 μm were prepared in the same manner as in Comparative Example 1 except that the aging conditions were changed to 130° C. and 24 hours.

[0142] <Comparative Example 6>

[0143] A varnish of a polymer composition and a sealing sheet of a polymer composition having a thickness of 50 μm were prepared in the same manner as in Comparative Example 2 except that the aging conditions were changed to 130° C. and 24 hours.

[0144] <Comparative Example 7>

[0145] A varnish of a polymer composition and a sealing sheet of a polymer composition having a thickness of 50 μm were prepared in the same manner as in Comparative Example 3 except that the aging conditions were changed to 130° C. and 24 hours.

[0146] <Water Content of Polymer Composition Layer>

[0147] The sealing sheets prepared in the examples and comparative examples were cut into 70 mm long and 40 mm wide, the support and the protective sheet were peeled off from the cut sealing sheets, the obtained polymer composition layer was folded and placed in a dried threaded tube bottle ("VABH17" manufactured by Mitsubishi Chemikarnary Tech Co., Ltd.), and loaded into an electric furnace ("VA-236S" manufactured by Mitsubishi Chemikarnary Tech Co., Ltd.) directly connected to a Karl Fischer measuring instrument ("CA310" manufactured by Mitsubishi Chemikarnary Tech Co., Ltd.). In a N2 gas flow, the temperature of the electric furnace was raised to 250°C, and the water separated from the measured sample was captured in a Karl Fischer measuring solution, and the mass of the water was measured according to a conventional method. Based on the mass of the measured water, the water content (ppm) of the polymer composition layer was calculated relative to the mass of the entire polymer composition layer. The results are shown in the following table.

[0148] The water vapor intrusion barrier properties of the polymer composition layer of each sealing sheet obtained in Examples and Comparative Examples were evaluated by the following method.

[0149] <Evaluation method of water vapor intrusion barrier properties>

[0150] As a support, a composite film having an aluminum foil and a polyethylene terephthalate film ("PET Tsuki AL1N30" manufactured by Tokai Toyo Aluminum Sales Co., Ltd., with an aluminum foil thickness of 30 μm and a PET film thickness of 25 μm) was prepared (the water vapor permeability of the composite film was 0.001 (g / m 2 / 24hr) or less).

[0151] A test sheet having a laminated structure of "support (composite film) / polymer composition layer / protective sheet (laminated film)" was obtained in the same manner as in the Examples and Comparative Examples except that the composite film was used as a support. It should be noted that the polymer composition layer was formed on the aluminum foil of the composite film.

[0152] A 50 mm×50 mm square glass plate made of alkali-free glass was prepared, washed with boiled isopropyl alcohol for 5 minutes, and dried at 150° C. for 30 minutes or more.

[0153] Calcium was deposited on one side of the dried glass plate using a mask covering an edge region at a distance of 0 mm to 2 mm from the end of the glass plate. Thus, a calcium film (purity: 99.8%) with a thickness of 200 nm was formed in the central portion of the one side of the glass plate except for the edge region at a distance of 0 mm to 2 mm from the end of the glass plate.

[0154] The polymer composition layer of the test sheet was bonded to the calcium film side of the glass plate using a hot press ("LAMIPAC DAISY A4 (LPD2325)" manufactured by Fujipro Corporation) in a nitrogen atmosphere to obtain a laminate. This laminate was used as an evaluation sample.

[0155] Generally speaking, if calcium contacts water to form calcium oxide, it becomes transparent. In addition, in the aforementioned evaluation samples, the glass plate and the aluminum foil have sufficiently high water vapor intrusion barrier properties, so moisture usually moves in the in-plane direction (direction perpendicular to the thickness direction) through the end of the polymer composition layer and reaches the calcium film. If moisture reaches the calcium film, the calcium film is oxidized from the end in sequence and becomes transparent, so the shrinkage of the calcium film is observed. Therefore, the intrusion of moisture into the evaluation sample can be evaluated by measuring the sealing distance (mm) from the end of the evaluation sample to the calcium film. Therefore, the evaluation sample containing the calcium film can be used as a model of an electronic device.

[0156] First, the initial sealing distance X2 (mm) from the end of the evaluation sample to the end of the calcium film was measured using a microscope (“Measuring Microscope MF-U” manufactured by MITSUYO Corporation).

[0157] Next, the evaluation sample is placed in a constant temperature and humidity chamber set to a temperature of 85°C and a humidity of 85% RH. The evaluation sample is taken out of the constant temperature and humidity chamber when the sealing distance X1 (mm) from the end of the evaluation sample placed in the constant temperature and humidity chamber to the end of the calcium film increases by 0.1 mm compared to the initial sealing distance X2. The time from the time the evaluation sample is placed in the constant temperature and humidity chamber to the time the evaluation sample is taken out of the constant temperature and humidity chamber is calculated as the reduction start time t (hours). This reduction start time t is equivalent to the time T from when the evaluation sample is placed in the constant temperature and humidity chamber P1 The sealing distance X1 (mm) between the end of the evaluation sample stored in the constant temperature and humidity chamber and the end of the calcium film becomes "X2 + 0.1 mm" T P2 The time till now.

[0158] The sealing distance X1 and the reduction start time t are substituted into the Fick diffusion equation of formula (1), and a constant K as a water vapor intrusion barrier parameter is calculated.

[0159] [Mathematical formula 1]

[0160]

[0161] The obtained constant K is used to evaluate the ability of the polymer composition layer to inhibit water intrusion (water vapor intrusion barrier) according to the following criteria. The smaller the value of the constant K, the higher the water vapor intrusion barrier. It should be noted that the following "hr" means "hour". The results are recorded in the following table. It should be noted that the following table "(cm / hr ^0.5)" means "(cm / hr 0.5 )".

[0162] (Standard for water vapor penetration barrier)

[0163] ○: Constant K is less than 0.02 cm / hr 0.5

[0164] ×: Constant K is 0.02 cm / hr 0.5 above

[0165]

[0166]

[0167]

[0168] As shown in the above table, Examples 1 to 4, which used a large amount of calcium oxide and formed an olefin polymer having a crosslinked structure, were able to form a polymer composition layer having a low water content and excellent water vapor intrusion barrier properties. On the other hand, Comparative Examples 1 to 7, which used semi-calcined hydrotalcite, calcined hydrotalcite, magnesium oxide, or molecular sieve 4A as a hygroscopic filler, could not sufficiently reduce the water content of the polymer composition layer. In particular, in Comparative Examples 5 to 7, aging for 24 hours was also performed, but the water content of the polymer composition layer could not be sufficiently reduced.

[0169] Industrial Applicability

[0170] The sealing sheet of the present invention is useful for sealing electronic devices (for example, organic EL devices, solar cells, sensor devices, etc.), conductive substrates, and the like.

[0171] This application is based on Japanese Patent Application No. 2020-125483 filed in Japan, the entire contents of which are incorporated herein by reference.

Claims

1. A sealing sheet having a laminated structure comprising a support, a polymer composition layer and a protective sheet in this order, The polymer composition layer includes an olefin polymer having a cross-linked structure, calcium oxide, and an olefin polymer not having a cross-linked structure. The content of the olefin polymer having a crosslinked structure is 1 to 40% by mass relative to 100% by mass of the nonvolatile components of the polymer composition layer. The content of calcium oxide is 40% by mass or more and 80% by mass or less relative to 100% by mass of the nonvolatile components of the polymer composition layer, The content of the olefin polymer having no crosslinking structure is 5 to 50% by mass relative to 100% by mass of the nonvolatile components of the polymer composition layer, and When the sealing sheet is produced, the water content of the polymer composition layer is 250 ppm or less based on the mass of the entire polymer composition layer. Drying of the sealing sheet before sealing can be omitted.

2. The sealing sheet according to claim 1, wherein The content of calcium oxide is 40% by mass or more and 70% by mass or less relative to 100% by mass of the nonvolatile component of the polymer composition layer.

3. The sealing sheet according to claim 1 or 2, wherein When the sealing sheet is produced, the water content of the polymer composition layer is 100 ppm or less based on the mass of the entire polymer composition layer.

4. The sealing sheet according to claim 1 or 2, wherein The olefin polymer having a crosslinked structure is formed of an olefin polymer having a carboxyl group and / or an acid anhydride group and an olefin polymer having an epoxy group.

5. The sealing sheet according to claim 1 or 2, wherein The water vapor permeability of the support and the protective sheet is 1g / m 2 / 24hr or less. The sealing sheet according to claim 1 or 2, which is used for sealing electronic devices.

7. The sealing sheet according to claim 6, wherein The electronic device is an organic EL device or a solar cell.

8. A polymer composition layer comprising an olefin polymer having a cross-linked structure, calcium oxide, and an olefin polymer not having a cross-linked structure, The polymer composition layer is used to manufacture a sealing sheet, The content of the olefin polymer having a crosslinked structure is 1 to 40% by mass relative to 100% by mass of the nonvolatile components of the polymer composition layer. The content of calcium oxide is 40% by mass or more and 80% by mass or less relative to 100% by mass of the nonvolatile components of the polymer composition layer, The content of the olefin polymer having no crosslinking structure is 5 to 50% by mass relative to 100% by mass of the nonvolatile components of the polymer composition layer, and When the sealing sheet is produced, the water content of the polymer composition layer is 250 ppm or less based on the mass of the entire polymer composition layer. Drying of the sealing sheet before sealing can be omitted.

9. The polymer composition layer according to claim 8, wherein The content of calcium oxide is 40% by mass or more and 70% by mass or less relative to 100% by mass of the nonvolatile component of the polymer composition layer.

10. The polymer composition layer according to claim 8 or 9, wherein When the sealing sheet is produced, the water content of the polymer composition layer is 100 ppm or less based on the mass of the entire polymer composition layer.

11. The polymer composition layer according to claim 8 or 9, wherein The olefin polymer having a crosslinked structure is formed of an olefin polymer having a carboxyl group and / or an acid anhydride group and an olefin polymer having an epoxy group.

Citation Information

Patent Citations

  • Discharge lamp lighting device

    JP1982012509B2

  • JP1982019106B2

  • Organic electroluminescent element and its manufacturing method

    JP2006269247A

  • Method for producing gas barrier film

    JP2013108103A

  • Gas barrier film

    JP2016185705A